Increase of Serum γ-Glutamyltransferase Associated With Development of Cirrhotic Cystic Fibrosis Liver Disease. (July 2015) - Bodewes, Frank A.J.A.; van der Doef, Hubert P.J.; Houwen, Roderick H.J.; Verkade, Henkjan J.
ABSTRACT: Background: Identification of patients at risk for developing cirrhotic cystic fibrosis liver disease (CCFLD) is essential for targeting potentially preventive treatment. We studied the evolution of serum liver enzymes and thrombocyte counts as predictors of CCFLD development. Methods: For this study, we defined the diagnosis of CCFLD as the combination of splenomegaly (on either physical examination or ultrasound scan) and macronodularity of the liver on ultrasound scan. We reviewed the medical records of 277 pediatric patients with CF for the diagnosis of CCFLD. In each patient with CCFLD, we reviewed serum liver enzymes and thrombocyte counts in the 2-year period preceding the diagnosis of CCFLD. We compared these results with a non-CCFLD control group (patients with CF older than 15 years with no reported signs or symptoms of CCFLD). Results: In the 2 years preceding the diagnosis, the γ-glutamyltranspeptidase (GGT) levels of patients with CCFLD were significantly higher compared to non-CCFLD controls (42 ± 5 vs 17 ± 2 U/L, respectively; P < 0.001). Corresponding aspartate aminotransferase and alanine aminotransferase levels did not significantly differ between patients with CCFLD and controls. The thrombocyte counts in patients with CCFLD were significantly lower than those in controls (252 ± 108 vs 320 ± 94 × 10 9 /L, respectively; P < 0.05). The predictive value for CCFLD of a single GGT measurement was low; however, for patients with CF with a mean GGT > 35 U/L, based on repeated measurements, the odds ratio for developing CCFLD was 39 (95% confidence interval 9–175, specificity was 95%, sensitivity was 64%, positive predictive value was 50%). For the thrombocytes, however, no reliable cutoff value could be identified. Conclusions: In pediatric patients with CF, a persistently high-normal GGT is strongly associated with the diagnosis of CCFLD within 2 years. The prognostic value of a single GGT measurement is limited, but repeated GGT measurements may allow the identification of groups of patients at increased risk for CCFLD.